2015
DOI: 10.4049/jimmunol.1500473
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Regulatory Networks between CD8 T, B, and Myeloid Cells in Organ Transplantation Tolerance

Abstract: In transplantation tolerance, numerous regulatory populations have the capacity to inhibit allograft rejection; however, their compensatory capacities have never been clearly evidenced. We have previously demonstrated that the tolerogenic effect mediated by CD8+CD45RClow regulatory T cells (Tregs) in a model of organ transplantation with CD40Ig could be abrogated by permanent depletion of CD8+ cells that resulted in allograft rejection in half of the recipients. This result demonstrated that CD8+ Tregs were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Clinical protocols applying polyclonal or antigen-specific CD4 + Treg cell therapy in transplantation are underway and hold promise, but results are not yet available (36). In the last years, we have investigated the properties of a population of CD8 + Tregs that arise in a model of cardiac allograft tolerance following blocking of CD40-CD40L interactions (18,20,21,23,24,(37)(38)(39) and are characterized by the low expression or absence of the CD45RC marker, which is one of the less known and studied alternative splice variants of the CD45 molecule.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical protocols applying polyclonal or antigen-specific CD4 + Treg cell therapy in transplantation are underway and hold promise, but results are not yet available (36). In the last years, we have investigated the properties of a population of CD8 + Tregs that arise in a model of cardiac allograft tolerance following blocking of CD40-CD40L interactions (18,20,21,23,24,(37)(38)(39) and are characterized by the low expression or absence of the CD45RC marker, which is one of the less known and studied alternative splice variants of the CD45 molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Rat spleens were harvested at day 120, and splenocytes or subpopulations were purified as previously described (18,23 A Canto II cytometer (BD Biosciences) was used to measure fluorescence, a FACS Aria II (BD Biosciences) was used to sort cells, and data were analyzed using the FLOWJO software (Tree Star Inc.). Cells were first gated by their morphology excluding dead cells by selecting DAPI-viable cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients receiving autologous HSCT for systemic sclerosis, increased numbers of Breg cells (defined as CD19 + CD24 hi CD38 hi ) were reported at 6 and 12 months post transplant with no alteration in the levels of Foxp3 + CD25 hi CD4 + Treg cells . Regulatory networks between B and T cells, and a role for interleukin‐10 (IL‐10) ‐producing Breg cells, have been reported in a clinical graft‐versus‐host disease model following cord blood transplantation …”
Section: Introductionmentioning
confidence: 98%
“…36 We have also shown that IL-34, a recently discovered cytokine involved in monocyte/macrophage differentiation, was secreted by approximately half of FOXP3 + CD8 + and CD4 + Tregs. 39 Other more classical cytokines such as TGFβ have also been described as playing a role in CD8 + Treg suppressive activity. This was the first description of a role for this cytokine in T cell biology and transplantation.…”
Section: Main Char Ac Teris Ti C S Of Cd8 + Reg Ul Atory T Cell Smentioning
confidence: 99%